Constraints Analysis of MAHAGRAPES Farmers - Nikam Vinayak Ramesh , Premlata Singh , Shiv Kumar andRakesh E.S., (Indian Journal of Extension Education, 2014)
Mahagrapes is a marketing partner to a group of grape growers' cooperative societies in Maharashtra. It helps grapegrowers in exporting their produce to European countries. The study was aimed at analysing constraints faced byMahagrapes members during production and export of grapes. Nashik, Sangli and Pune districts of Maharashtra werepurposively selected for data collection. Data were collected by focused group discussion and personal interview ofmembers and constraints were ranked using Garrett's ranking technique. The study revealed that major constraints facedby farmers were difficulty in following recommended practices, absence of produce procurement policy, lack of pricepolicy for grapes by the Government, non-availability of labour during peak season and more incidence of pests anddiseases.